Penerapan Metode Vouching Pada Audit Investigatif Atas Siklus Pengeluaran : (Studi Kasus pada PT XYZ) - Duta Rahma Safira; Gideon Setyo Budiwitjaksono (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Business competition is increasing from time to time, encouraging companies to make financial reports as accurate as possible. These conditions cause companies to try various ways to create good financial reports by acting outside the limits, such as manipulating financial statements which are classified as fraud. The effort that must be made to detect and disclose fraud is an investigative audit that is carried out to detect fraud by collecting and analyzing evidence. PT XYZ as a client of KAP Y is a company in the field of logistics services that requires investigative audit services to reveal indications of fraud that occurred. This research aims to analyze the application of the vouching method in the investigative audit process of the expense cycle. The approach used in this research is a case study-based qualitative approach. The data used is secondary data through interviews with KAP Y auditors. Through the vouching method, the auditor can find fraud that occurs at PT XYZ in the expenditure cycle. The auditor found that there was a large amount of funds spent for unknown reasons and there was no valid evidence that could explain the use of these funds.